PREVALENCIA DE HIDATIDOSIS HUMANA MEDIANTE TÉCNICAS DE IMAGEN EN YANAHUANCA, PASCO. - Chumbe G., Elizabeth (2010)
The objective of this study was to determine the prevalence of human echinococcosis in nine communities of the district of Yanahuanca, Pasco, through abdominal echography and thorax radiography. In addition, the association between age, gender, and community with the disease was evaluated. Echographic examination was conducted in 949 persons (52% of the population over 5 years of age) and X ray test was performed in 829 (45.6%). The overall prevalence of human cystic echinococcosis was 5.5% (52/949) and the 95% confidence interval varied from 4.1 to 7.1%. There was statistical association (p<0.05) between age with positive results when using the ultrasound exam. The liver / lung hydatid cyst ratio was 5:1. Partial or total calcified cysts were detected by echographical examination (56%, 25/45). The prevalence of human hydatidosis in this endemic area of Peru is one of the highest in Latin America, possibly due to the close interaction with dogs, as they shepherd the flocks, plus poor sanitation and hygiene conditions in the area.